Emergency Computed Tomography: How Misinterpretations Vary According to the Periods of the Nightshift?. Issue 2 (28th March 2021) - Platon, Alexandra; Etienne, Leonard; Herpe, Guillaume; Yan, David; Massoutier, Maximilien; Perneger, Thomas; Becker, Minerva; Poletti, Pierre-Alexandre
Abstract : Objective: To evaluate the accuracy of initial computed tomography (CT) interpretations made by radiology residents during nightshifts in the emergency department. Methods: Preliminary CT reports performed by radiology residents during 120 consecutive nightshifts (08:30 pm to 08:30 am ) were reviewed, attendings' final interpretation being the reference standard. Nightshifts were divided into four consecutive periods of 3 hours. Major misinterpretations were related to potentially life-threatening conditions if not treated immediately after CT. The rate of misinterpretations was calculated for all CT examinations, separately for nightshift's periods and for residents' training years. Results: Misinterpretations were recorded in 155 (7.4%) of 2102 CT examinations, 0.6% (13/2102) were major. There were 2.2% (4/186) major misinterpretations that occurred during the last period of the nightshift versus 0.4% (9/1916) during the first periods of the night ( P < 0.05). Of all misinterpretations, 8.5% (130/1526) were made by third- and fourth-year residents and 4.3% (25/576) by fifth-year residents ( P < 0.005). Conclusions: Major misinterpretations occur at the end of the nightshift, which may be explained by the fatigue effect. The rate of misinterpretations is lower among fifth-year residents, which may be related to their prior experience in reading emergency cases.